ANALISIS KESULITAN BELAJAR MATEMATIKA PADA MATERI PENJUMLAHAN PECAHAN BERPENYEBUT BEDA PADA SISWA KELAS V MI NW REBAN TEBU - Sri Wahyuni; Muslihan; EM. Thonthowi Jauhari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to identify and analyze the learning difficulties experienced by fifth-grade students at MI NW Reban Tebu in the topic of addition of fractions with unlike denominators. The research method applied is a case study using data collected through observations, interviews, and documentation of students' test scores. The findings reveal that students face significant challenges in understanding the concept of fractions, especially in finding common denominators, operating the principles of fraction mathematics, and solving word problems involving fraction operations. The predominantly lecture-based teaching method is less effective in enhancing students' motivation and understanding. Furthermore, low learning motivation and an unconducive learning environment exacerbate their learning difficulties. Teachers have employed visual media and remedial teaching as strategies to address these challenges; however, there is a need for more innovative and supportive learning approaches. This study recommends implementing interactive and participatory teaching methods, complemented by family involvement, to improve student achievement. The integration of such methods is expected to foster a more supportive learning atmosphere, enhance student engagement, and ultimately improve mathematical proficiency, particularly in fraction operations. This research provides valuable insights for educators and policymakers striving to enhance elementary mathematics education, especially around challenging concepts like fractions with unlike denominators.